Design, Production and Comparison with Theoretical Calculations of a Uniform Electromagnetic Field Generator with Helmholtz Coils - Avcı, Ferdi; Ağrali, Emin; Yaman, Orhan; Çavaş, Mehmet (Niyazi BULUT, 2025)
[Abstract Not Available]
Keywords: Metroloji; Uygulamalı ve Endüstriyel Fizik